Physical discipline in Samoan families : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Social Work, Massey University - Hunt-Ioane, Faye (Massey University, 2005)
Child Maltreatment in Samoan Families of New Zealand examines parenting and childrearing in the context of Samoan families in New Zealand. It is apparent that each culture has its own parenting and childrearing methods. For Samoans, their child rearing practices in relation to physical discipline have been brought under scrutiny by New Zealand society. This situation has created an environment of challenge in the media and assumed cultural practice not only from non-Samoans but also from within the Samoan community regarding physical discipline in the Samoan home. This thesis takes an in-depth look at the use of physical discipline in Samoan parenting and child rearing. The literature review looks at past and current events of physical discipline in New Zealand. It places the Samoan community in context to this literature and how that relates to their families. This research is supported with data drawn from twelve Samoan leaders in the community through a qualitative interview. These twelve leaders have come from different cross sectors of employment ranging from Government departments to community agencies. They were selected specifically on the basis of their highly regarded reputation and passion to work with Samoan families in the community. The qualitative interviews indicated that physical punishment as a means of discipline was an issue of concern among Samoan parents in the community since it was viewed as the most preferred method to bring about effective change to unacceptable behaviour. The implications of this research can only make the Samoan community aware of the reality of their parenting and childrearing methods in their families and advance as a community looking at alternatives to physical punishment. In doing so, they take ownership of and responsibility for their disciplinary methods and address it in the constructs of Fa'asamoa within the family. The relationship with the children is retained as well as their Samoan heritage whilst living in New Zealand. The greatest significance of this thesis will be to those of Samoan ethnicity since this research embraces the heart of their cultural values and beliefs, 'their collective families'. Any research that addresses physical discipline goes to the heart of Samoan households because it targets their children and youth. Samoan children and youth do not come in isolation from their families; clearly a child needs to be examined and understood in the context of this unit. The thesis concludes with a Samoan response to section 59, of the Crimes Act 1961 and how Samoans would see the repealing of this section being appropriately addressed in the Samoan community. It also puts forward recommendations to government to advise policy how best to work with the Samoan community on the issue of physical punishment in the home. It is my hope in the conclusion of this research that whoever picks up this piece of work will have a greater understanding and insight to Samoan parenting and childrearing within a cultural context, but more importantly how to work effectively in a culturally appropriate model that will bring about conducive changes that will not only benefit Samoan families but any government agency and community group that works with Samoan people. Before one places a judgment on any cultural group its takes more than just a day to walk in their shoes to fully grasp and appreciate what it means to be Samoan! I challenge the reader to put aside his or her own cultural expectations and judgements to understand the heart-felt passion and difficulty of my journey in presenting this information to my Samoan community.
Keywords: Samoans, New Zealand; Child maltreatment; Samoan children, New Zealand; Child discipline